Impact of Covid-19 on Social Security Allowance Beneficiaries’ Families in Nepal - Dangal, Hemanta; Acharya, Durga (Journal of Social Protection, 2023)
This study illustrates the impact of the Corona Virus Disease (Covid-19) pandemic on beneficiaries of social security allowance following the adoption of preventive measures like message alerts, imposition of lockdown, restriction in movement, and social distancing. The study covers social security allowance beneficiaries of ten local levels from different parts of Nepal. Telephone survey was conducted with the representative sample population which was randomly selected from the social security allowance beneficiaries ‘list. Findings show that the majority of respondents had received messages related to Covid-19, and half of the population had knowledge of where to approach in case of health emergency. The income of many households declined due to loss of jobs during the lockdown. About half of the population had received small relief support from the local government and humanitarian agencies. The food stock was low due to lack of sufficient money to purchase and high inflation rate. The social security allowance payment was delayed and one fourth of the beneficiaries were uncertain about the next payment. In overall, the social security allowance beneficiaries including their family members, suffered during the Covid-19 and were at risk of food insecurity.